Quality indicators for colonoscopy procedures: a prospective multicentre method for endoscopy units. - Romain Coriat (PLoS ONE, 2012)
Background and aims Healthcare professionals are required to conduct quality control of endoscopy procedures, and yet there is no standardised method for assessing quality. The topic of the present study was to validate the applicability of the procedure in daily practice, giving physicians the ability to define areas for continuous quality improvement. Methods In ten endoscopy units in France, 200 patients per centre undergoing colonoscopy were enrolled in the study. An evaluation was carried out based on a prospectively developed checklist of 10 quality-control indicators including five dependent upon and five independent of the colonoscopy procedure. Results Of the 2000 procedures, 30% were done at general hospitals, 20% at university hospitals, and 50% in private practices. The colonoscopies were carried out for a valid indication for 95.9% (range 92.5-100). Colon preparation was insufficient in 3.7% (range 1-10.5). Colonoscopies were successful in 95.3% (range 81-99). Adenoma detection rate was 0.31 (range 0.17-0.45) in successful colonoscopies. Conclusion This tool for evaluating the quality of colonoscopy procedures in healthcare units is based on standard endoscopy and patient criteria. It is an easy and feasible procedure giving the ability to detect suboptimal practice and differences between endoscopy-units. It will enable individual units to assess the quality of their colonoscopy techniques.